Interdyscyplinarna Pracownia Prawa Medycznego i Bioetyki (2013–2015) - Wnukiewicz-Kozłowska, Agata (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Interdisciplinary Medical Law and Bioethics Research Centre was founded in 2013, on the basis of Rector’s order No. 106/2013. This entity is dedicated to the legal and ethical problems of medicine, biology and biotechnology. Activities of the centre are concentrated on research, education and popularization of issues connected with the development of medical technologies which is very rapid and bringing about difficulties and tensions stemming from both legal and ethical points of view. Interdisciplinary cooperation is very important for the evolution of the centre and that is why one of its main features is involvement in its activities of a group of lawyers, physicians and academics from different universities and research institutions.
Keywords: Interdyscyplinarna Pracownia Prawa Medycznego i Bioetyki; Wydział Prawa Administracji Ekonomii UWr; historia